The functional dimension of crusade literature: A comparative perspective - Jaran, Mahmoud; Khaldi, Asef (Research Journal in Advanced Humanities, 2024)
From the late eleventh century to the present, the Crusades had a profound impact on popular culture, politics and imagination. Drawing on recent studies, this article explores the functional dimension of literature regarding the Crusades in both European vernacular and Arabic contexts. It argues that literary representations of the Crusades serve distinct purposes within each cultural sphere while also highlighting shared motifs and themes. These representations vary in their functions from historical documentation to political exhortation, as seen in Arabic medieval poetry, troubadour poems and Torquato Tasso’s Jerusalem Delivered. The study underscores the significance of literature in shaping political consciousness, showing how it transcended artistic boundaries to become social and political instrument. The comparative analysis of these two literary traditions highlights their shared focus on the use of literature as a means of influencing political thought and action, despite their differing cultural contexts.